(untitled) (Revista de História da UEG (REVHIST), 2023)
This article makes an analysis, based on state law 9.554/2022, which entitles the Ananindeua Island as “Cultural Heritage of an Intangible nature” in the state of Pará. Our study is based on the following problematic: how the legislation can mobilize the discussion around the cultural and natural heritage, in regions historically excluded from these debates, and also the federal instrument of heritage safeguard? In this context based on an interview with the person responsible for creating Project and Law, we can identify importance of legislative incentive for the protection of the culture and natural heritage, but some social and political problematic involving the Ananindeua archipelago and safeguard of some cultural assets in the region. Keywords: Amazonia. Ananindeua Island. Cultural Landscape. Natural Heritage.